Smart Growth at the Ballot Box: Understanding Voting on Affordable Housing and Land Management Referendums. Issue 6 (November 2020) - Pearson-Merkowitz, Shanna; Lang, Corey
This study investigates voter decision-making on two smart-growth components: land preservation and affordable housing. We seek to understand how voters make concurrent decisions about unpaired smart-growth components at the ballot box. Previous studies of smart growth, affordable housing, and environmental preservation have focused primarily on describing the attitudes and traits of voters on these policies, utilize aggregate voting outcomes, or are case studies of single towns in which there is a fairly homogenous group of residents either supporting or opposing the policy. We draw on a unique data set to investigate the different covariates of attitudes for environmental preservation and affordable housing: an exit poll of voters in the 2016 Rhode Island General Election on bond referendums for environmental preservation and affordable housing. We find that the coalition for smart growth that includes both land preservation and affordable housing is undermined by views of minorities and the poor as undeserving.